Touch the science of the sense that makes us human - Linden, David J. (Penguin Books, 2016)
Touch is the sense that makes us human. If you are born blind or deaf, your body and brain will mostly develop normally and you can live a rich life. But deprive a baby of social touch and they will have higher life-long levels of stress and fear. From why brushing fingers with a waiter will make you leave a larger tip, to why a hot drink in a job interview improves your chances, this is a mesmerising journey into our senses. With surprising stories and cutting-edge research on pleasure and pain, it shows how touch shapes our sense of self and bonds us together.